Pathogenesis Based Diagnosis and Treatment of Endometriosis - Koninckx, Philippe R.; Fernandes, Rodrigo; Ussia, Anastasia; Schindler, Larissa; Wattiez, Arnaud; Al-Suwaidi, Shaima; Amro, Bedayah; Al-Maamari, Basma; Hakim, Zeinab; Tahlak, Muna (Frontiers in Endocrinology, 2021)
Understanding the pathophysiology of endometriosis is changing our diagnosis and treatment. Endometriosis lesions are clones of specific cells, with variable characteristics as aromatase activity and progesterone resistance. Therefore the GE theory postulates GE incidents to start endometriosis, which thus is different from implanted endometrium. The subsequent growth in the specific environment of the peritoneal cavity is associated with angiogenesis, inflammation, immunologic changes and bleeding in the lesions causing fibrosis. Fibrosis will stop the growth and lesions look burnt out. The pain caused by endometriosis lesions is variable: some lesions are not painful while other lesions cause neuroinflammation at distance up to 28 mm. Diagnosis of endometriosis is made by laparoscopy, following an experience guided clinical decision, based on history, symptoms, clinical exam and imaging. Biochemical markers are not useful. For deep endometriosis, imaging is important before surgery, notwithstanding rather poor predictive values when confidence limits, the prevalence of the disease and the absence of stratification of lesions by size, localization and depth of infiltration, are considered. Surgery of endometriosis is based on recognition and excision. Since the surrounding fibrosis belongs to the body with limited infiltration by endometriosis, a rim of fibrosis can be left without safety margins. For deep endometriosis, this results in a conservative excision eventually with discoid excision or short bowel resections. For cystic ovarian endometriosis superficial destruction, if complete, should be sufficient. Understanding pathophysiology is important for the discussion of early intervention during adolescence. Considering neuroinflammation at distance, the indication to explore large somatic nerves should be reconsidered. Also, medical therapy of endometriosis has to be reconsidered since the variability of lesions results in a variable response, some lesions not requiring estrogens for growth and some being progesterone resistant. If the onset of endometriosis is driven by oxidative stress from retrograde menstruation and the peritoneal microbiome, medical therapy could prevent new lesions and becomes indicated after surgery.